Emerging Market Multinationals’ Home Non-Market Advantages and their Subsidiaries’ Strategic Responses to Institutions in a Host Emerging Country Environment - Becker-Ritterspach, Florian (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2018.